Policy Analysis and Models of Strengthening the Regional Economy Post Covid 19 in North Sumatra Province - Muhammad Yusuf; Jumiadi AW; Sulaiman Lubis; Azizul Kholis (International Journal of Economic, Technology and Social Sciences (Injects), 2022)
This study aims to see how strategic policies can be carried out in meeting the regional economy after the COVID-19 pandemic, both from fiscal strategy and monetary strategy. This research is a field/empirical research with a quantitative approach based on primary and secondary data. The population of this study is all State and Private Universities in North Sumatra Province. For the Regional Government represented by the Statistical Management Agency, the sampling technique is based on judgment Sampling, namely population members are selected based on the consideration of the ease of data collection by the researcher. The results of the research and the results of the analysis show that fiscal policy and monetary policy affect the strengthening of the economy, It is known that fiscal policy affects the strengthening of the economy more than monetary policy, this indicates that the government must pay attention to fiscal policy in strengthening the economy.